The Mayflower secret - Jackson, Dave.; Jackson, Neta.; Jackson, Julian (Minneapolis, Minn. : Bethany House Publishers, 1998)
Teenage Elizabeth Tilley, one of the colonists landing at New Plymouth on the Mayflower, sees her parents die from illness and wonders if God is punishing her for the terrible secret she carries.
"Ages 8-12"--P. [4] of cover.
Keywords: Tilley, Elizabeth, -- 1607-1687 or 1688 -- Juvenile fiction; Pilgrims (New Plymouth Colony) -- Juvenile fiction; Tilley, Elizabeth, -- 1607-1687 or 1688 -- Fiction; Pilgrims (New Plymouth Colony) -- Fiction; Massachusetts -- History -- New Plymouth, 1620-1691 -- Fiction; Orphans -- Fiction; Christian life -- Fiction